Change Management Model for Effective Use of Examination Administration System: Developing Country Case Study - Mphahlele, Ngoanamosadi Stanford; Kekwaletswe, Raymond Mompoloki; Seaba, Tshinakaho Relebogile (Universitas Bina Darma, 2024)
There is inadequate knowledge on change management model (CMM) for post-acceptance phase of information systems. This paper intends to determine and model change management factors (CMFs) that explain effective use of Examination Administration System (EAS) in South Africa. A survey was used to collect data from 215 EAS users in Technical and Vocational Education and Training colleges and was analyzed quantitatively. Empirical results evince existence of casual nexuses between user involvement and change recognition, user satisfaction, performance measurement with use of EAS which through EAS adaptive use (EAU) in turn together with EAS verification, user learning representational fidelity and informed actions influence effective use of EAS. This study results add to literature by explaining the indirect mechanisms (i.e., EAS and EAU) through which the CMFs can influence effective use. This paper also offers a novel integration of Effective Use Theory and Unified Theory of Acceptance and Use of Technology with three CMFs which provides a holistic model. This study recommends that various communities endeavour to use CMM as a guide to influence user communities to effectively use information systems in diverse contexts. The model also has potential to drive improved return on investments and enhance employees’ productivity.